Computer simulation of beam dynamics on JINR phasotron up to 660 MeV energy - Onischenko, L.M.; Samsonov, E.V. (Вопросы атомной науки и техники, 2006)
Project of increasing the beam intensity of the 660 MeV JINR Proton Phasotron by an external injection of the H - beam with energy 5 MeV is now under design. Process of the beam injection was investigated formerly. Investigation of the acceleration process up to the final energy is reported in this paper. It is found that the beam losses exist along the acceleration.